Dyplomacja i wywiad USA wobec powstania i działalności Karty 77 - Tyszkiewicz, Jakub (1966– ) (Instytut Historii PAN, 2025)
The emergence and development of Charter 77 in Czechoslovakia attracted significant interest in the United States, aligning with the new role of human rights in President Jimmy Carter’s policy toward Eastern Europe between 1977 and 1980. Declassified documents from the US embassy in Prague and intelligence sources shed new light on the evolution and activities of Charter 77. The American mission provided detailed reports on the dissidents’ activities, also drawing on statements from individuals associated with the new movement. These new sources further illustrate the impact of Charter 77 on the overall political situation in Czechoslovakia, including the regime’s and society’s reactions to the dissidents. They also enable a deeper understanding of Charter 77’s role within the broader US policy toward Prague during that period.
p. 143-167
Summary in English.
Keywords: Charter 77; human rights in Czechoslovakia; US-Czechoslovak relations; US diplomacy and intelligence; United States - foreign relations - Czechoslovakia 1970-2000; Czechoslovakia - foreign relations - United States 1970-2000; United States. Central Intelligence Agency - 1970-2000